Studies in theoretical physics. - Erenso, Daniel; Montemayor, Victor (Victor J.) (IOP (Series). Release 22., 2022)
Studies in Theoretical Physics, Volume 1: Fundamental mathematical methods is the first of the six-volume series in theoretical physics. It provides the mathematical methods that any physical sciences and engineering undergraduate might need in upper-division courses in classical mechanics, quantum mechanics, and electricity and magnetism.